Characterizing the Deacidification Adsorption Model of Organic Acids and Phenolic Compounds of Noni Extract Using Weak Base Ion Exchanger. (5th June 2018) - Hashim, Haslaniza; Zubairi, Saiful Irwan; Wan Mustapha, Wan Aida; Maskat, Mohamad Yusof
Abstract : Although noni ( Morinda citrifolia L.) has been used to treat a broad range of diseases, many people avoid consuming the fruits because of its unpleasant odor caused by organic acids. Even though ion exchange resins were able to reduce the odor, it also reduced beneficial antioxidant compounds. Thus, to preserve antioxidants (phenolic compounds) during deacidification, it is important to characterize the interaction of ion exchange resin with both organic acids and phenolic compounds. Adsorption capacities of organic acids and phenolic compounds commonly found in the noni fruit were conducted onto Amberlite IRA 67 resin. The phase contact time to reach equilibrium for octanoic acid and hexanoic acid compounds was 326.86 and 160.72 min, respectively. The values of initial adsorption rate, 1 / K 1, and adsorption extent, 1 / K 2, decreased with the increase of initial concentration for all compounds studied. Results for all the compounds studied fitted well to the Langmuir model. The effect of pH in adsorption capacity of the actual system (noni juice) has been applied based on the model system studied.